Impact of effluent organic matter on low-pressure membrane fouling in tertiary treatment - Ayache, C.; Pidou, M.; Croué, Jean-Philippe; Labanowski, J.; Poussade, Y.; Tazi-Pain, A.; Keller, J.; Gernjak, W. (IWA Publishing, 2013)
This study aims at comparing low-pressure membrane fouling obtained with two different secondary effluents at bench and pilot-scale based on the determination of two fouling indices: the total fouling index (TFI) and the hydraulically irreversible fouling index (HIFI). The main objective was to investigate if simpler and less costly bench-scale experimentation can substitute for pilot-scale trials when assessing the fouling potential of secondary effluent in large scale membrane filtration plants producing recycled water. Absolute values for specific flux and total fouling index for the bench-scale system were higher than those determined from pilot-scale, nevertheless a statistically significant correlation (r2 = 0.63, a = 0.1) was obtained for the total fouling index at both scales. On the contrary no such correlation was found for the hydraulically irreversible fouling index. Advanced water characterization tools such as excitation-emission matrix fluorescence spectroscopy (EEM) and liquid chromatography with organic carbon detection (LC-OCD) were used for the characterization of foulants. On the basis of statistical analysis, biopolymers and humic substances were found to be the major contribution to total fouling (r2 = 0.95 and r2 = 0.88, respectively). Adsorption of the low molecular weight neutral compounds to the membrane was attributed to hydraulically irreversible fouling (r2 = 0.67).